The Asian financial crisis New International Financial Architecture: Crisis, reform and recovery - Sharma, Shalendra D (Manchester University Press, 2003)
The Asian financial crisis of 1997-98 shook the foundations of the global economy. What began as a localised currency crisis soon engulfed the entire Asian region. What went wrong and how did the Asian economies, long considered 'miracles', respond? How did the United States, Japan and other G-7 countries react to the crisis? What role did the IMF play? Why did China, which suffers from many of the same structural problems responsible for the crisis, remain conspicuously insulated from the turmoil raging in its midst? What explains Asia's remarkable recovery just three years after the crisis? In what fundamental ways did the Asian crisis serve as a catalyst to the current thinking about the 'new international financial architecture'? What lessons can be learnt from the crisis by other emerging economies? This book provides answers to all the above questions and more. It gives a comprehensive account of how the international economic order operates, examines its strengths and weaknesses, and what needs to be done to fix it. The book will be vital to students of economics, international political economy, Asian and development studies.